Assessment of Self Esteem and Peer Pressure among Adolescents in Selected College of Kanchipuram District, Tamil Nadu (Indian Journal of Public Health Research & Development, 2020)
A descriptive study to assess of self esteem and peer pressure among adolescents in a selected collegeKanchipuram district Tamil Nadu. The objectives are to assess self esteem and peer pressure amongadolescents. To find out the association between levels of self esteem and peer pressure among adolescentsand selected demographic variables of adolescents. The sampling technique was non probability purposivesampling. Sample size was 132 samples of adolescents. Rosenberg self esteem scale was used to assess selfesteem and peer pressure inventory by brown to assess peer pressure. The demographic variables performa,structured interview schedule to collect data. The data collection was done. The collected data was tabulatedand analyzed, using descriptive and inferential statistics. The self esteem mean value is 21.9 and peerpressure mean value is 8.1.
Keywords: Self esteem, peer pressure, Adolescents.